Isatin come on the stage of CDK4/6 inhibitor - Pradana, Radiktya Surya; Fareza, Muhammad Salman (Pharmacy Reports, 2022)
Cyclin-dependent kinase (CDK) 4/6 inhibitors have significantly improved the prognosis for patients with hormone receptor-positive (HR+) and human epidermal growth factor receptor 2-negative (HER2-) breast cancer, including those with metastatic or advanced breast cancer (mBC/ABC). Recent research has focused on developing CDK4/6 inhibitors with diverse structural frameworks, including isatin-based compounds. Isatin and its derivatives have shown promise in inhibiting CDK4/6, with potential efficacy against breast cancer cell lines. Studies have also indicated that isatinyl-2-aminobenzoylhydrazone (ISABH) complexes, particularly those with transition metals like nickel (Ni-ISABH), exhibit strong binding affinities to CDK6 and fulfill key pharmacokinetic criteria.